Strategic Control of Corporate Development Under Ambiguous Circumstances - Ruefli, Timothy; Sarrazin, Jacques (Management Science, 1981)
The theory of corporate strategic decision-making has traditionally been dominated by a planning orientation. The corporation was assumed to have reliable information and few strategic constraints over its development horizon. While this approach may have been relevant during the 1950's and 1960's, the emergence of public interest groups and increased activities of government agencies in the 1970's and 1980's has constrained corporate influence and has increased the ambiguity in the environment for strategic decisions. This state of affairs has been noted in a general manner by practitioners and some theorists. This paper, after reviewing various approaches to strategic decision-making, develops an analytic model that places corporate development in a control framework. In this new approach managers are not required to set precise long-range goals nor is the information required expected to be as reliable in the long run as it is in the short run, nor equally reliable across all dimensions of decision-making. The strategic control approach links a relatively ambiguous long-range environment to a more certain short run environment through the concept of a mid-range corporate development window. Planning per se is then a short-range process directed, not at precise long-range goals, but rather at a mid-range performance window the attainment of which will position the corporation so that it will have a high probability of reaching the loosely defined set of long-range goals. Strategic control is a new framework for assessing the theory and guiding the practice of strategic decision making for corporate development.